Civic Responsibility Pedagang Kaki Lima dalam Kepatuhan Peraturan Daerah Kota Bandung Nomor 11 Tahun 2024 tentang Penataan dan Pemberdayaan PKL - Najma Zahira Devianti; Prayoga Bestari; Dadi Mulyadi Nugraha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the implementation of civic responsibility among Street Vendors (PKL) in the implementation of Bandung City Regional Regulation Number 11 of 2024 concerning the Arrangement and Empowerment of Street Vendors. The study employed a qualitative approach using a case study method in the Jalan Saparua area, Bandung City. Participants were determined through purposive sampling, including officers from the Civil Service Police Unit (Satpol PP), the Office of Cooperatives and SMEs, and street vendors. Data were collected through in-depth interviews, observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that the implementation of civic responsibility among street vendors has not been optimal, as reflected in the low understanding of regulations, weak legal awareness and social responsibility, and participation that tends to be conditional and pragmatic. These conditions still lead to violations of street vendor arrangement regulations in the research area. In addition, economic factors and the need to maintain livelihoods also influence the level of compliance of street vendors with regional regulations. Therefore, educational, participatory, and empowerment-based handling strategies are needed to achieve sustainable compliance and create urban order and environmental comfort.